Cardiopulmonary resuscitation during the COVID-19 pandemic: a scientific statement on CPR management protocol of Kasr Al-Ainy University Hospital is presented - Hesham S. Taha; Mirna M. Shaker; Mohamed M. Abdelghany (The Egyptian Heart Journal, 2020)
Abstract Background The COVID-19 pandemic poses a major burden to the healthcare system in Egypt, and in the face of a highly infective disease which can prove fatal, healthcare systems need to change their management protocols to meet these new challenges. Main body This scientific statement, developed by the cardiology department at Cairo University, emphasized 6 different aspects that are intended to guide healthcare providers during cardiopulmonary resuscitation (CPR) in the era of the COVID-19 pandemic. It highlighted the importance of dealing with all cardiac arrest victims, during the pandemic, as potential COVID-19 cases, and the use of appropriate personal protective equipment (PPE) by health care providers during the procedure. It also stated that the CPR procedure should be done in a separate room with the door closed and that the number of providers present during the procedure should be limited to only those who are essential for patient resuscitation. It also stressed that family members and accompanying personnel of patients with possible COVID-19 should not be in the vicinity of CPR site. The statement also pointed out that CPR procedure should be done in the standard manner with precautions to minimize spread of infection to the staff and accompanying people. Early intubation was prioritized, and the use of rapid sequence intubation with appropriate PPE was recommended. For delivery of CPR for the prone ventilated patient, delivery of chest compressions by pressing the patient’s back, while a team prepares to turn the patient supine, was recommended. During intra-hospital transport, it was emphasized that the receiving intensive care unit (ICU) should be notified about the possibility of the patient being COVID-19 positive, so that appropriate infection control precautions are taken. Conclusion Cardiopulmonary resuscitation of cardiac arrest patients in the COVID-19 era poses a significant challenge, and all health care providers should deal with any cardiac arrest victim presenting to the emergency department as potential COVID-19 suspects and should use the appropriate PPE.